2018
DOI: 10.14499/indonesianjcanchemoprev9iss3pp134-142
|View full text |Cite
|
Sign up to set email alerts
|

Pentagamaboronon-0 Fructose Inhibited Migration and Overexpression of Matrix Metalloproteinases 9 on MCF-7/HER2 Breast Cancer Cells

Abstract: The incidence of Breast Cancer Metastasis (MBC) can be categorized in stage IV as well as being the leading cause of death in cases of breast cancer. MBC prognosis is known to be weak, frequent recurrent, and MBC patients have only a survival rate of about 5 years. One of the proteins that causes breast cancer metastasis is Human Epidermal Growth Factor 2 (HER2). Pentagamaboron-0 (PGB-0), a newly curcumin analogue performed cytotoxic effect on HER2-positive breast cancer cells but it is practically water-insol… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 12 publications
0
5
0
Order By: Relevance
“…This showed that EEKP has promising anticancer potential. In addition, KP displayed a cytotoxic effect on HeLa, SKOV3, HuCCA-1, RMCCA-1, and T24 cancer cell lines [18,19,[21][22][23]. Given that the cytotoxic activity of KP in highly metastatic breast cancer cells has never been reported before, our findings are novel.…”
Section: Discussionmentioning
confidence: 83%
See 3 more Smart Citations
“…This showed that EEKP has promising anticancer potential. In addition, KP displayed a cytotoxic effect on HeLa, SKOV3, HuCCA-1, RMCCA-1, and T24 cancer cell lines [18,19,[21][22][23]. Given that the cytotoxic activity of KP in highly metastatic breast cancer cells has never been reported before, our findings are novel.…”
Section: Discussionmentioning
confidence: 83%
“…The MTT assay was carried out based on previous study with modifications on 4T1, MCF-7, and NIH-3T3 cell line [19]. 4T1 and MCF-7 cells are breast cancer cell models, whereas NIH-3T3 cells are noncancerous cell line models.…”
Section: Determination Of Cytotoxic Activity Using Mtt Assaymentioning
confidence: 99%
See 2 more Smart Citations
“…Irradiation of neutron beam to the boron compound causes the boron-10 atoms to split to Li nuclei and alpha radiation (He nuclei) which only give intracell effects within cancer cells [8,9,11,[31][32][33][34] as shown in Fig. 6 [35,36].…”
Section: Discussionmentioning
confidence: 99%